2017
DOI: 10.36216/jpd.v1i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Konsumsi Purin Tinggi Dengan Hiperurisemia: Suatu Penelitian Potong Lintang Pada Penduduk Suku Bali di Kota Denpasar

Abstract: Latar Belakang: Hiperusemia adalah istilah yang menggambarkan kadar asam urat darah di atas normal. Konsumsi purin tinggi merupakan salah satu faktor yang erat kaitannya dengan hiperurisemia. Tujuan: Penelitian ini bertujuan untuk mengetahui adanya hubungan konsumsi purin tinggi dengan hiperurisemia pada penduduk suku Bali di kota Denpasar. Metode: Penelitian ini adalah studi potong lintang analitik yang dilakukan pada bulan Juli sampai dengan September 2004. Populasi pada penelitian ini adalah pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
1
4
0
2
Order By: Relevance
“…Prevalence of hyperuricemia in the study was higher in comparison to studies from other countries such as US (21.4%), China (8.4%), Northeast China (10.85%), Thailand (10.46%).2, [14][15][16] In comparison to other big cities (Depok and Denpasar; 18.6% and 18.2%. respectively) in Indonesia, prevalence of hyperuricemia in this rural area was also higher.3, 4 Genetic might influence hyperuricemia prevalence in this study. A study in Northern Sulawesi, Indonesia presented that genetic is considered as one of prominent risk factors (OR 14.42 (8.01-26.23) p < 0.0001).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Prevalence of hyperuricemia in the study was higher in comparison to studies from other countries such as US (21.4%), China (8.4%), Northeast China (10.85%), Thailand (10.46%).2, [14][15][16] In comparison to other big cities (Depok and Denpasar; 18.6% and 18.2%. respectively) in Indonesia, prevalence of hyperuricemia in this rural area was also higher.3, 4 Genetic might influence hyperuricemia prevalence in this study. A study in Northern Sulawesi, Indonesia presented that genetic is considered as one of prominent risk factors (OR 14.42 (8.01-26.23) p < 0.0001).…”
Section: Discussionsupporting
confidence: 45%
“…In Depok City, West Java, prevalence of hyperuricemia was 18.6%, while in Denpasar, Bali the prevalence was 18.2%. 3,4 Balance between uric acid production and renal excretion determines the level of serum uric acid. Multiple factors such as race or inheritance, gender, age, obesity, hormones, dietary changes including greater of purine-rich processed foods, alcohol, fructose, lifestyles, and increasing use of diuretics affect serum uric acid level and eventually prevalence of hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian yang dilakukan di kota Denpasar, Bali mendapatkan prevalensi hiperurisemia sebesar 18,2%. (5) Hiperurisemia ini dapat menyebabkan inflamasi vaskuler, proliferasi otot polos, peningkatan produksi renin, dan lesi vaskuler pada ginjal. Lebih jauh lagi hiperurisemia akan menyebabkan perubahan mikrovaskuler pada ginjal yang mirip dengan gambaran arteriosklerosis pada hipertensi esensial.…”
Section: Hiperurisemiaunclassified
“…[7] Food consumption patterns of Balinese people are generally in the form of processed foods containing high purines such as pork lawar, chicken betutu, chicken or pork steam, pork satay and grill pork which have the potential to increase uric acid levels and lead to hyperuricemia. [8] The study by Indrawan (2005) found the prevalence of hyperuricemia in Denpasar City at 18.2%. [9] Another study conducted by Diana (2007) found the prevalence of hyperuricemia in the Nusa Ceningan community at 17% .…”
Section: Introductionmentioning
confidence: 99%
“…[8] The study by Indrawan (2005) found the prevalence of hyperuricemia in Denpasar City at 18.2%. [9] Another study conducted by Diana (2007) found the prevalence of hyperuricemia in the Nusa Ceningan community at 17% . [10] Studies on the relationship between intake of purine and blood uric acid levels have been carried out in Bali, but as far as the researchers know, similar studies with postmenopausal female respondents have never been conducted in Denpasar City.…”
Section: Introductionmentioning
confidence: 99%